Cultures of Reciprocity and Cultures of Control in the Circumpolar North - Anderson, David G. (Journal of Northern Studies, 2014)
This article surveys different cultures of engagement between people, animals, and the landscape across the circumpolar Arctic. Through ethnographic examples the article describes offering rituals and placings in several Arctic contexts in the light of the emphasis they place on affirming personhood. Similarly, rituals of management and regulation are described in the terms of how they strive to create predictability and control. The article tries to mediate this contrast by examining “architectural” examples of co-operation and co-domestication between humans, animals and landscapes. The article concludes with a reflection on how the themes of “origins” and “animal rights” further reconstruct these dichotomies.